Participação do sistema endocanabinoide da substância cinzenta periaquedutal dorsolateral em um modelo animal de pânico - Thércia Guedes Viana (2012)
Glutamate is a neurotransmitter that facilitates defensive responses related to anxiety and panic, through the activation of N-methyl-d-aspartate receptors (NMDA, named after the selective agonist). On the contrary, the endocannabinoid anandamide is a neurotransmitter that inhibits such reactions. Several brain regions are involved in these responses, including the periaqueductal gray (PAG). Considering the evidence that endocannabinoids inhibit the glutamatergic neurotransmission, the present work tested the hypothesis that the activation of cannabinoid CB1 receptors could inhibit the panicogenic effects of NMDA injected into the dorsolateral PAG (dlPAG) in rats. The animals underwent stereotactic surgery for implantation of the cannula in dlPAG and after 7 days their behaviour was analyzed in an observation box. NMDA injection into the dlPAG produced escape reactions characterized by an increase in the number of crossings and jumps. This effect was prevented by local injection of a CB1 agonist, ACEA, or an anandamide-hydrolysis inhibitor, URB-597. In addition, URB-597 also prevented the increase in Fos protein expression, a marker of neural activation, induced by NMDA. All the effects of this anandamide-hydrolysis inhibitor were blocked by a CB1 receptor antagonist, AM251. It is concluded that cannabinoid CB1 receptors modulate defensive responses induced by NMDA receptor activation in the dlPAG.